The Role of Modern Pedagogical Technologies in Teaching Foreign Language (French Language) for Non-Philology Students (in the Topic of “Le Sport Et La Vie Saine”) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article reveals the role of modern pedagogical technologies in teaching a foreign language (French) to students of non-philological specialties based on the topic “Le sport et la vie saine” (“Sport and healthy living”).